CURRICULAR CONTEXT IN EDUCATION CYCLES: THE IMPACT OF EDUCATIONAL CHANGES ON THE PEDAGOGICAL ACTIONS OF PHYSICAL EDUCATION TEACHERS (Fiep Bulletin - online, 2015)
This study focuses on the pedagogical action of the physical education teacher on the everyday life of the school in “Education Cycles”. The objectives were to identify and understand the way that pedagogical know-how is built in the City of Porto Alegre Education Network. It is a case study, oriented by a qualitative perspective. The analysis and interpretation of the information show an innovative pedagogical proposition and express a real and practicable option to improve the quality of education. However, this proposition presents some diverging aspects in its application, allowing the uprising contradictions.
Keywords: Pedagogical Accion; Physical Education Teachers; Formation Cycles